2021
DOI: 10.1080/1331677x.2020.1867215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of privacy concern, risk, and information control in a smart tourism destination

Abstract: Smart tourism destinations are growing, with the use and implementation of technology to make travel more enjoyable. Still, the tourist's information privacy concerns generated by the big data available to the destination and service providers is a significant problem for smart tourism, which can affect the sustainability and economic benefit of the smart tourism destination. This study investigates privacy concern, perceived risk, control of information, service provider trust in a smart tourism destination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
1
8
1
1
Order By: Relevance
“…10)". Secondly, the SPPI affects the perception of smart tourism applications, a finding which is in line with the study of Afolabi et al [73]. The level of SPPI affects the PSTA, and the SPPI is different for different platforms of smart tourism applications: "Meituan, Ctrip, Yilong: these (applications) are still more reliable, I think.…”
Section: Qualitative Study Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…10)". Secondly, the SPPI affects the perception of smart tourism applications, a finding which is in line with the study of Afolabi et al [73]. The level of SPPI affects the PSTA, and the SPPI is different for different platforms of smart tourism applications: "Meituan, Ctrip, Yilong: these (applications) are still more reliable, I think.…”
Section: Qualitative Study Resultssupporting
confidence: 80%
“…Furthermore, some studies have shown that tourists' PSTA can affect tourist satisfaction and TH [17,69]. Meanwhile, PSTA is likely to involve tourists' SPPI [73]. Thus, whether PSTA can play a mediating role between SPPI and TH is a question that should be explored.…”
Section: Perception Of Smart Tourism Application (Psta)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, participation rates are lower for immigrants, especially for immigrant women. Other research findings have also emphasised the significance of gender differences when analysing migration in Europe (Afolabi et al, 2021;Vorobeva & Dana, 2021). Based on this finding, the female participation rate has also been considered a possible significant factor in migrating the population from the Nordic countries to Germany.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Xiang et al (2015), Huang et al (2017), andGonzález-Reverté et al (2018), among others, warn of the privacy and security risks related to the use of smart technologies. In particular, location-based services (LBSs) have raised great concern due to the use of the location of users by mobile applications that, in some cases, ends up negatively affecting trust in destinations (Afolabi et al 2021).…”
Section: Smart Tourism Technologymentioning
confidence: 99%